The Role Of Marketing Strategy In Improving Consumer Purchase Decisions On Employee Performance At Labbaik Chicken Kampung Bali - Evi Herlyaminda; Annisa Rahma Putri (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the role of marketing strategies in increasing consumer purchasing decisions and their impact on employee performance at Labbaik Chicken Kampung Bali. Effective marketing strategies are believed not only to attract consumer interest but also to contribute to increased sales volume, ultimately influencing employee motivation and performance. This research employs a quantitative approach using surveys targeting consumers and observations of employee performance at Labbaik Chicken Kampung Bali. Data were collected through questionnaires distributed to 200 active consumer respondents, as well as in-depth interviews with employees and relevant management. Data analysis techniques used multiple linear regression and hypothesis testing to examine the influence of marketing strategy variabels (including product, price, promotion, and place) on employee performance, as well as the relationship between purchasing decisions and employee performance. The research findings indicate that marketing strategies have a significant negative effect on employee performance. However, conversely, an increase in purchasing decisions positively impacts employee performance, particularly regarding productivity, job satisfaction, and loyalty toward the company. This study provides managerial implications for Labbaik Chicken Kampung Bali to continuously optimize its marketing strategies as an integral part of human resorce development and business sutainability.